KEABSAHAN SERTIFIKAT HAK ATAS TANAH DALAM PASAL 32 AYAT (2) PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997: ANTARA KEABSAHAN ADMINISTRATIF DAN KEABSAHAN MATERIIL - Ni Kadek Febri Dewi Tirani; I Kadek Dony Hartawan; Ni Komang Irma Adi Sukmaningsih (Universitas Pendidikan Ganesha, 2026)
Land registration is intended to ensure legal certainty through the issuance of land title certificates, which serve as legally recognized evidence of land rights. Article 32(2) of Government Regulation No. 24 of 1997 provides legal protection to landowners and certificate holders who acquire land rights in good faith and exercise actual physical possession of the land, provided that the certificate has been lawfully issued. However, the regulation does not specify the legal parameters of the phrase